2022
DOI: 10.3389/fped.2022.895074
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies the Extremely Rare ITGAV and FN1 Variants in Early Onset Inflammatory Bowel Disease Patients

Abstract: BackgroundMolecular diagnosis of early onset inflammatory bowel disease (IBD) is very important for adopting suitable treatment strategies. Owing to the sparse data available, this study aims to identify the molecular basis of early onset IBD in Arab patients.MethodsA consanguineous Arab family with monozygotic twins presenting early onset IBD was screened by whole exome sequencing (WES). The variants functional characterization was performed by a series of computational biology methods. The IBD variants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Song et al [ 65 ] showed that ADH1C is downregulated in UC. FN1 was suggested by Al-Numan [ 66 ] to be related to the early onset of IBD. SPINT2 plays a role in epithelial adhesion [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [ 65 ] showed that ADH1C is downregulated in UC. FN1 was suggested by Al-Numan [ 66 ] to be related to the early onset of IBD. SPINT2 plays a role in epithelial adhesion [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, studying the familial cases may uncover rare causal variants, their heritability of disease in unrelated patient cohorts is still uncertain (23). Unlike VEO-IBD, which has a causal monogenic factor, late-onset is a complex and multifactorial disorder that cannot be explained by classical genetic segregation methods (16,24,25). Large-scale sporadic case-control studies on WES-based rare variant burden analysis (RVB) have previously identified several strong risk loci for complex diseases, such as Schizophrenia ( 26), Alzheimer's disease (27), epilepsy (2019), autism (28), and Crohn's disease (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to better understand the pathogenesis of complex diseases, application of next-generation sequencing technologies is having a greater impact, especially in consanguineous societies (15)(16)(17). They will provide an excellent opportunity to identify rare variants with intermediate to high effect ranges more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…These results will pave the way for future prediction/validation of DNA and RNA binding proteins affected in human disorders through AlphaFold-predicted structures modeling and refined stereochemistry experiments at atomic resolution [ 18 , 19 ]. This article represents the first report of a de novo mutation underpinning a PURA syndrome in a Latin American patient and highlights the importance of predicting the molecular effects on protein structure with artificial intelligence and advanced molecular chemistry algorithms.…”
Section: Introductionmentioning
confidence: 99%